Future warming and acidification effects on anti‐fouling and anti‐herbivory traits of the brown alga Fucus vesiculosus (Phaeophyceae). Issue 1 (1st November 2016) - Raddatz, Stefanie; Guy‐Haim, Tamar; Rilov, Gil; Wahl, Martin
Abstract : Human‐induced ocean warming and acidification have received increasing attention over the past decade and are considered to have substantial consequences for a broad range of marine species and their interactions. Understanding how these interactions shift in response to climate change is particularly important with regard to foundation species, such as the brown alga Fucus vesiculosus . This macroalga represents the dominant habitat former on coastal rocky substrata of the Baltic Sea, fulfilling functions essential for the entire benthic community. Its ability to withstand extensive fouling and herbivory regulates the associated community and ecosystem dynamics. This study tested the interactive effects of future warming, acidification, and seasonality on the interactions of a marine macroalga with potential foulers and consumers. F. vesiculosus rockweeds were exposed to different combinations of conditions predicted regionally for the year 2100 (+∆5°C, +∆700 μatm CO2 ) using multifactorial long‐term experiments in novel outdoor benthic mesocosms ("Benthocosms") over 9–12‐week periods in four seasons. Possible shifts in the macroalgal susceptibility to fouling and consumption were tested using consecutive bioassays. Algal susceptibility to fouling and grazing varied substantially among seasons and between treatments. In all seasons, warming predominantly affected anti‐fouling and anti‐herbivory interactions while acidification had a subtle nonsignificant influence. Interestingly, anti‐microfouling activity was highest during winter under warming, while anti‐macrofouling and anti‐herbivory activities were highest in the summer under warming. These contrasting findings indicate that seasonal changes in anti‐fouling and anti‐herbivory traits may interact with ocean warming in altering F. vesiculosus community composition in the future.